Gestão estratégica e as competências gerenciais na estrutura organizacional do departamento de marketing. Um estudo de caso em uma indústria de bebidas - Baisch, Lindiane da Veiga (2009)
The present work presents a case study, in a beverage industry, in Santa Maria, RS, which uses Strategic Planning in its activities. The goal of this research is to identify the managing competences of the Marketing Manager of the studied company. In order to achieve this goal, the main Strategic Management Models and the current Marketing department structure models were studied, the Strategic Planning, the Organizational Structure and the Marketing Department were analyzed as well as the present and expected Roles and the Competences of the Marketing Manager of the studied company. In order to collect data, a structured interview was used, based on open and close questions, applied to the Marketing Manager, his/her superiors and subordinates. With these interviews, it was possible to identify the way the company s marketing structure is organized, as well as to analyze the managing competences that this professional has and should have, for and efficient perform of his/her functions and the optimization of the company s Strategic Management